MODEL PENGEMBANGAN LOMPAT TINGGI GAYA STRADDLE MENGGUNAKAN PERMAINAN LOMPAT TALI PADA SISWA KELAS IV SD NEGERI GAJAH MUNGKUR 02 KOTA SEMARANG TAHUN PELAJARAN 2012/2013 (Department of Physical Education, Sport, Health and Recreation, 2013)
Straddle-style high jump game is still taught in the raw form of the game to be recovered is stillless active students in learning the high jump, students still feel scared at draftsmanship andlimitations of the Sarpras So there should be a modification in the learning process. This researchmethod is the research on the development and expansion of the model that is developerrevenue jump rope game. As for product development procedures include analysis of productswill be developed, developing the initial product, and revision of validation, testing and revisionof the small group, large group trials and the final product. Data collection was done usingfield observations and questionnaires obtained from the evaluation and the results of the questionnaireby the students filling. Data analysis technique used is descriptive percentage. Fromthe experimental results obtained percentage of the average size of the product analysis resultsPenjas 82.00% (good), learning of 87.00% (good), a small group of trial 83.00% (good), andfield test 87, 10% (good). Based on the research results, it is concluded that the jump rope gamescan be used as an alternative game Penjas teacher in learning penjasorkes.